Solvothermal synthesis of polyvinyl pyrrolidone encapsulated, amine-functionalized copper ferrite and its use as a magnetic resonance imaging contrast agent - Heydari, Fatemeh; Ilosvai, Ágnes M.; Kovács, Noémi; Máthé, Domokos; Kristály, Ferenc; Daróczi, Lajos; Kaleta, Zoltán; Viskolcz, Béla; Nagy, Miklós; Vanyorek, László; Forgách, László; Szigeti, Krisztián (PLOS ONE, 2025)
Copper ferrite nanoparticles for use as MRI contrast agents were synthesized using two different methods. A novel microwave-assisted (MW) solvothermal method was developed and compared to a conventional 12-hour synthesis (Reflux) as an eco-friendlier approach. This innovative synthesis method successfully produced nanoparticles with enhanced properties compared to traditional ferrite materials. The nanoparticles’ morphological and magnetic properties were evaluated and tested in in-vivo MRI studies. The results revealed both similarities and differences between the amine-functionalized copper ferrite nanoparticles. FTIR, XRD, HRTEM, and VSM analyses indicated improved properties in the CuFe2O4-NH2 MW particles, while AFM confirmed successful polymer encapsulation of the nanoparticles. For the CuFe2O4-NH2 MW sample, 76.8 wt% copper ferrite and 23.2 wt% magnetite were detected, with crystallite sizes of 8 ± 2 nm and 13 ± 2 nm, respectively. In the CuFe2O4-NH2 Refl. sample, in addition to these two magnetic phases, larger copper particles (31.6 wt%) were also formed. DLS analysis demonstrated that the CuFe2O4-NH2 MW sample exhibited excellent colloidal stability, maintaining its size distribution in aqueous media for 3 hours without aggregation, unlike the CuFe2O4-NH2 Refl. sample, which showed slight aggregation. The CuFe2O4-NH2 MW sample displayed superparamagnetic behavior (Ms: 15 emu/g, Mr: 0 emu/g, Hc: 0 Oe), while the CuFe2O4-NH2 Refl. sample exhibited ferromagnetic characteristics (Ms: 40 emu/g, Mr: 1.35 emu/g, Hc: 30 Oe). Both samples produced comparable results during in vitro MRI measurements, showing similar T2* relaxation and signal characteristics. Further in vivo studies demonstrated that both samples induced significant hypointense changes. The study provides valuable insights into the synthesis, properties, and potential applications of these materials, emphasizing the importance of eco-friendly methods and the optimization of ferrite-based MRI contrast agents.